2017
DOI: 10.1038/srep41203
|View full text |Cite
|
Sign up to set email alerts
|

The expression of SIRT1 regulates the metastaticplasticity of chondrosarcoma cells by inducing epithelial-mesenchymal transition

Abstract: SIRT1 belongs to the mammalian sirtuin family and plays an important role in deacetylating histone and nonhistone proteins. It is reported that SIRT1 is associated with tumor metastasis in several kinds of tumors. However, the effect of SIRT1 on the metastasis of chondrosarcoma cells is still unknown. In this study, we demonstrated that up and down-regulation of SIRT1 expression could significantly change the invasive and metastatic potential in chondrosarcoma cell line. Besides that, the result from the nude … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…The expression of GAPDH was measured as an internal control. Thermocycler conditions included an initial hold at 50 °C for 2 minutes and then 95 °C for 10 minutes followed by a two-step PCR programme of 95 °C for 15 seconds and 60 °C for 60 seconds repeated for 40 cycles on an Mx4000 system (Applied Biosystems, Foster City, CA), on which data were collected and quantitatively analysed 79 . The expression level of mRNA was demonstrated as the fold change relative to the control group 80 .…”
Section: Enrichment Analysis Of Gene Ontology and Kegg By Gene Set Enmentioning
confidence: 99%
“…The expression of GAPDH was measured as an internal control. Thermocycler conditions included an initial hold at 50 °C for 2 minutes and then 95 °C for 10 minutes followed by a two-step PCR programme of 95 °C for 15 seconds and 60 °C for 60 seconds repeated for 40 cycles on an Mx4000 system (Applied Biosystems, Foster City, CA), on which data were collected and quantitatively analysed 79 . The expression level of mRNA was demonstrated as the fold change relative to the control group 80 .…”
Section: Enrichment Analysis Of Gene Ontology and Kegg By Gene Set Enmentioning
confidence: 99%
“…SIRT1 regulates the metastatic plasticity. 51 Chao et al have reported that SIRT1 signalling is induced by resveratrol, a natural phenolic compound found in several plants, 52 and induces human chondrosarcoma cell apoptosis. 53 Taken these reports, the role of SIRT1 in chondrosarcoma is still not clear.…”
Section: Sirtuin-1mentioning
confidence: 99%
“…Therefore, SirT1 plays many biological roles, including the inhibition of cell differentiation, cell cycle regulation, apoptosis inhibition and tumorigenesis [17,18]. Notably, the expression of SirT1 is upregulated in several cancers including leukemia, colon cancer, prostate cancer, and lung cancer [7,8,19,20]. However, the exact effect of SirT1 in cancer development is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Sirtuin, the mammalian silent information regulator 1 family, is a molecular family that includes seven members (SirT1 to SirT7, respectively) and shares extensive homologies with the silent information regulator 2 (sir2) gene in yeast [7]. SirT1, located in the cell nucleus, is the closest homologue of sir2 and a well-documented member of the sirtuin family [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation